Adaptation to Work from Home under Situation Covid-19 Crisis: A Case Study Personnel of Sena District Office Ayutthaya Province - Meemuk, Nathaphan; Treemongkol, Patcha; Hongwijit, Suwannee; Laohapichartchai, Pornpisa (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
This research purpose for (1) To study the problems work from home under the COVID-19 crisis. (2) To study the environment in support work from home under the COVID-19 crisis. (3) Guidelines for adaptation to Work from Home under Situation Covid-19 Crisis: A Case Study Personnel of Sena District Office Ayutthaya Province. This research uses a qualitative research methodology. A Total of 10 Key Informants from personnel of Sena District Office Phra Nakhon Si Ayutthaya Province. The research instrument was In-depth Interviews with semi-structured Interviews. Triangulation data and data analysis with Content Analysis, Fishbone Diagram Analysis, and PESTEL Analysis methods. The findings showed that (1) the problem of work from home under the Covid-19 crisis is that personnel of the Sena District Office has never worked from home before there was a crisis of COVID-19. There is no preparation and a lack of knowledge and understanding. (2) The environment in support of work from home under the COVID-19 crisis found that The state policy does not have measures for officers who work from home that are good enough to make the work out as inefficient as it should be. Many Outsource workers of government organizations so taking turns going into the office to work. And personnel who looking want the organization to have support for equipment and facilities to be up to trend so that organizations at all levels can develop for work as well. (3) Guidelines for adaptation to Work from Home under Situation Covid-19 Crisis The government should have a concrete Work from Home policy that is appropriate for the situation and the health system should focus on balancing the health of workers between work at home and their private lives. Article history: Received 4 April 2023 Revised 11 August 2023 Accepted 14 August 2023 SIMILARITY INDEX = 1.58 %